Transport properties through double-magnetic-barrier structures in graphene - 王素新 李志文 刘建军 李玉现 (Chinese physics B, 2011)
We study electrons tunneling through a double-magnetic-barrier structure on the surface of monolayer graphene. The transmission probability and the conductance are calculated by using the transfer matrix method. The results show that the normal incident transmission probability is blocked by the magnetic vector potential and the Klein tunneling region depends strongly on the direction of the incidence electron. The transmission probability and the conductance can be modulated by changing structural parameters of the barrier, such as width and height, offering a possibility to control electron beams on graphene.